Reversion of methionine addiction of osteosarcoma cells to methionine independence results in loss of malignancy, modulation of the epithelial-mesenchymal phenotype and alteration of histone-H3 lysine-methylation - Aoki, Yusuke; Han, Qinghong; Tome, Yasunori; Yamamoto, Jun; Kubota, Yutaro; Masaki, Noriyuki; Obara, Koya; Hamada, Kazuyuki; Wang, Justin D.; Inubushi, Sachiko; Bouvet, Michael; Clarke, Steven G.; et al. (Frontiers in Oncology, 2022)
Methionine addiction, a fundamental and general hallmark of cancer, known as the Hoffman Effect, is due to altered use of methionine for increased and aberrant transmethylation reactions. However, the linkage of methionine addiction and malignancy of cancer cells is incompletely understood. The isogenic pair of methionine-addicted parental osteosarcoma cells and their rare methionine-independent revertant cells enabled us to compare them for malignancy, their epithelial-mesenchymal phenotype, and pattern of histone-H3 lysine-methylation. Methionine-independent revertant 143B osteosarcoma cells (143B-R) were selected from methionine-addicted parental cells (143B-P) by their chronic growth in low methionine culture medium for 4 passages, which was depleted of methionine by recombinant methioninase (rMETase). Cell migration capacity was compared with a wound healing assay and invasion capability was compared with a transwell assay in 143B-P and 143B-R cells in vitro. Tumor growth and metastatic potential were compared after orthotopic cell-injection into the tibia bone of nude mice in vivo. Epithelial-mesenchymal phenotypic expression and the status of H3 lysine-methylation were determined with western immunoblotting. 143B-P cells had an IC50 of 0.20 U/ml and 143B-R cells had an IC50 of 0.68 U/ml for treatment with rMETase, demonstrating that 143B-R cells had regained the ability to grow in low methionine conditions. 143B-R cells had reduced cell migration and invasion capability in vitro, formed much smaller tumors than 143B-P cells and lost metastatic potential in vivo, indicating loss of malignancy in 143B-R cells. 143B-R cells showed gain of the epithelial marker, ZO-1 and loss of mesenchymal markers, vimentin, Snail, and Slug and, and an increase of histone H3K9me3 and H3K27me3 methylation and a decrease of H3K4me3, H3K36me3, and H3K79me3 methylation, along with their loss of malignancy. These results suggest that shifting the balance in histone methylases might be a way to decrease the malignant potential of cells. The present results demonstrate the rationale to target methionine addiction for improved sarcoma therapy.